2020
DOI: 10.1038/s41467-020-17456-2
|View full text |Cite
|
Sign up to set email alerts
|

Decreased bioefficacy of long-lasting insecticidal nets and the resurgence of malaria in Papua New Guinea

Abstract: Papua New Guinea (PNG) has the highest malaria transmission outside of Africa. Longlasting insecticidal nets (LLINs) are believed to have helped to reduce average malaria prevalence in PNG from 16% in 2008 to 1% in 2014. Since 2015 malaria in PNG has resurged significantly. Here, we present observations documenting decreased bioefficacy of unused LLINs with manufacturing dates between 2013 and 2019 collected from villages and LLIN distributors in PNG. Specifically, we show that of n = 167 tested LLINs manufact… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(68 citation statements)
references
References 27 publications
1
50
0
1
Order By: Relevance
“…In Megiar, there was evidence that 2014 hotspots may have expanded by 2016, supporting observations from other settings that hotspots fuel ongoing transmission if neglected 32 , 33 . It is possible that the 2014 hotspots acted as a reservoir of infections at a time when LLINs with reduced bioefficacy 34 were distributed in the area in 2015 35 , thereby fuelling the expanded hotspot in 2016. Entomological data from the area also showed that infective biting rates were observed to increase by threefold in Megiar and 18-fold in Mirap between 2010 and 2016 and that the majority of vectors were caught outdoors (personal communication, J. Keven).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Megiar, there was evidence that 2014 hotspots may have expanded by 2016, supporting observations from other settings that hotspots fuel ongoing transmission if neglected 32 , 33 . It is possible that the 2014 hotspots acted as a reservoir of infections at a time when LLINs with reduced bioefficacy 34 were distributed in the area in 2015 35 , thereby fuelling the expanded hotspot in 2016. Entomological data from the area also showed that infective biting rates were observed to increase by threefold in Megiar and 18-fold in Mirap between 2010 and 2016 and that the majority of vectors were caught outdoors (personal communication, J. Keven).…”
Section: Discussionmentioning
confidence: 99%
“…This could suggest that vector biting was occurring at earlier times when individuals were not sleeping and therefore not under LLINs or biting outdoors as previously documented in PNG 46 , 47 and other settings 48 50 . Additionally, the reduced bio-efficacy of LLINs distributed in PNG since 2013 34 is likely to be a major contributing factor towards the lack of protective effect of LLIN when the third round of LLIN distribution occurred in this area in 2015 35 . This coincides with the resurgence observed in the surveyed villages in 2016.…”
Section: Discussionmentioning
confidence: 99%
“…Pyrethroid insecticides remain effective and are used in all WHO prequalified LLINs. Recent data from Papua New Guinea has also shown that just 17% of LLINs, with manufacturing dates prior to 2013, were fulfilling the WHO bioefficacy standards, suggesting their contribution to the resurgence of malaria in the country and warranting increased scrutiny of LLINs [ 27 ]. Although synergists such as piperonyl butoxide (PBO), have come into the market there remains a need to quickly and effectively monitor the residual concentration of insecticides to aid national Programmes in planning and implementing vector control interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Kegagalan penggunaan kelambu dalam upaya menurunkan penyakit tular vektor dapat disebabkan beberapa alasan antara lain: penggunaan/perawatan yang tidak tepat, 22 ketahanan fisik, 23 tingkat pengetahuan pengguna, tetapi dapat juga disebabkan penurunan efisiensi insektisida. 24 Kurangnya informasi tentang berbagai aspek biologi, perilaku dan status resistensi insektisida yang bersifat spesifik lokal, diduga menjadi salah satu penyebab fundamental berkembangnya penyakit tular vektor.…”
Section: Pembahasanunclassified